Trends in measures of handgrip strength from 2014 to 2017 among Korean adolescents using the Korean National Health and Nutrition Examination Survey Data - Kang, Yunkoo (BMC Res Notes, 2020)
OBJECT: Measuring handgrip strength is a useful method to evaluate sarcopenia. No study has shown the trends of handgrip strength to weight ratio among Korean adolescents by year. This study aimed to determine the trends of handgrip strength among Korean adolescents using data from the Korea National Health and Nutrition Examination Survey (KNHANES). Data of 2304 adolescents who participated in the KNHANES between 2014 and 2017 were obtained. The handgrip-to-weight ratios were categorized by age, sex, and year. RESULTS: Handgrip strength in adolescents decreased from 28.67 kg in 2014 to 27 kg in 2017 (P for trend < 0.05). The handgrip-to-weight ratio also decreased from 51.48 in 2014 to 48.18 in 2017 (P for trend < 0.05). The handgrip strength and handgrip-to-weight ratio also decreased among boys and girls over the years 2014–2017 (P for trend < 0.05). The results of the present study indicate that the handgrip-to-weight ratio decreased in Korean adolescents from the years 2014 to 2017, and a declining overall ratio indicates a decrease in the health status among Korean adolescents. Hence, there is a need to review the health status of Korean adolescents.